The Hemingway Narrative in the Spanish Civil War and Its Historical and Political Implications from Edward Said’s Theory - Octavio Tirado de Salazar, Rodrigo (2024)
This article consists in an historical analysis of three works by Ernest Hemingway that are set in the Spanish Civil War. The analysis is complemented by Edward Said’s theory called Orientalism to extract the narrative that the author proposes to be contrasted with the historical events to see how it is that the narrative that sought to unite the United States with the USSR to go together against fascism contributed to the illusion in which republican and democratic Spain of has being seen as a satellite state of the Soviet Union and, therefore, an enemy of the United States in the framework of the recently begun Cold War.